2011
DOI: 10.1163/138577211x587681
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of Bionanocomposites Based on Optically Active Poly(Ester-Imide) Containing L-Amino Acids Using Nano-ZnO Surface-Coupled by γ-Methacryloxypropyl-Trimethoxysilane

Abstract: In this paper, we investigated the synthesis of an optically active poly(ester-imide) containing two aminoacid residues in the main chain. This macromolecule was synthesized by polycondensation of N,N -(pyromellitoyl)-bis-L-tyrosine dimethyl ester as a diphenolic monomer and a chiral trimellitic anhydridederived diacid monomer containing L-methionine. The direct step-growth polymerization of this diacid with aromatic diol was carried out in a system of tosyl chloride (TsCl), pyridine (Py) and N,Ndimethylformam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In comparison with nanocomposite containing functionalized ZnO‐NPs by γ‐methacryloxypropyltrimethoxysilane (KH570) as a silane coupling agent, the TEM micrographs of obtained BNCs showed that NPs were uniformly dispersed in the PEI matrix. It has been recognized that the organic nature of coupling agent as a surface modifier is a key factor to promote the dispersion of the NPs in the polymer matrix 48…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with nanocomposite containing functionalized ZnO‐NPs by γ‐methacryloxypropyltrimethoxysilane (KH570) as a silane coupling agent, the TEM micrographs of obtained BNCs showed that NPs were uniformly dispersed in the PEI matrix. It has been recognized that the organic nature of coupling agent as a surface modifier is a key factor to promote the dispersion of the NPs in the polymer matrix 48…”
Section: Resultsmentioning
confidence: 99%
“…Poly(ester-imide)s (PEI)s have received considerable interest for their good heat resistance, mechanical properties, electrical insulation, chemical resistance and low melting viscosity [27][28][29] . These are widely used in electronic devices, membranes, adhesives, printed circuit boards, and engineering thermoplastics [30][31][32][33] .…”
Section: Studies On Preparation and Microstructure Characterization Omentioning
confidence: 99%
“…Poly(ester‐imide)s (PEI)s inherit desirable characteristics from both polyesters and polyimides. This class of polymers shows high thermal stability, good mechanical properties, facile processing, and electrical insulation . These properties have made them suitable for different applications in printed circuit boards, engineering thermoplastics, electronic devices, membranes, and adhesives .…”
Section: Introductionmentioning
confidence: 99%